Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The impact of using smart applications, “Sehaty application”, on health care at primary Care Center in Al-Qurayat regionMrs. Manal Abdulrhaman Ajina2. The impact of management transparency in promoting organizational loyalty – Field study on staff at The National Centre for Environmental complianceMr. Badr Faisal Al-Ghamdi3. The impact of the application of comprehensive quality standards on the performance of hospitals in The Kingdom of Saudi ArabiaMrs. Maysa Ehsan Tayb4. The Role of Talent Management Practices in Promoting the Creative Behavior:A Field Study on the Employees of the Saudi Electricity Company in AsirMr. Turki Aziz Abdullah Al Shumaylah, Co-Prof. Faisal Ahmed Abed Shuaibi5. The new international orientation towards a multipolar world: China and Russia as a modelMrs. Noura Ali Abdallah6. Testing the Relationship Between the Real Estate Market Index and the Saudi Stock Market Index for the Period from 2015 AD - 2022 ADMr. Ammar Suliman Fallatah, Asst-Prof. Haitham Zaker Khoj, Co-Prof. Hatem Khaled Akeel7. Monetary Policy and Stock Market Return: The Case of Saudi Arabia Interest Rates hikes  and Stocks ReturnsDr. Somaiyah Fahad Alalmai, Lecturer \ Alyaa Talal AlGhanmi
Keywords: Journal of Economic, Administrative and Legal Sciences